Antibiotic Use among Patients Visiting Primary Hospitals in Northwest Ethiopia: A Multicenter Cross-Sectional Survey - Adeladlew Kassie Netere; Ashenafi Kibret Sendekie (Advances in Pharmacological and Pharmaceutical Sciences)
Background. Antimicrobial medications are becoming ineffective because of the surge in antimicrobial resistance. Poor knowledge and inappropriate beliefs combined with the misuse of antibiotics may be common in the community and public health institutions. This study assessed the knowledge, belief, and antibiotic use practice among patients visiting rural hospitals in Northwest Ethiopia. Methods. A facility-based multicenter cross-sectional survey was conducted in Northwest Ethiopian primary hospitals from August to September 2020. The data are presented as frequencies and means (±SD) of our findings. The independent samples T test and One-Way Analysis of Variance (ANOVA) were used to explore the mean knowledge differences of antibiotic use among respondents. A pvalue of <0.05 with 95% CI was considered significant. Results. More than half of the participants (57.2%) were males, and the mean age was 34.8 ± 13.4 years. The mean (±SD) knowledge score of the respondents was 3.69 (±1.7) (range: 0 to 10), and the majority (69.7%) had poor knowledge. The mean (±SD) belief score (acceptance towards antibiotic use) of the respondents was 20.08 ± 4 (range: 7 to 35) and most (70.1%) of the respondents had moderate levels of perception regarding antibiotic use. The majority (69.5%) of respondents took antibiotics over the past year. Participants practiced inappropriate uses of antibiotics such as medication discontinuation (49.5%), keeping unused antibiotics for future use (35.5%), and sharing medications with/from others (30.1%). Diploma holder participants had significantly higher mean knowledge scores on antibiotic use than those who were unable to read and write (p=0.047). Similarly, students had higher mean knowledge scores compared with farmers (p=0.024), merchants (p=0.031), and housewives (p=0.047). Conclusion. Our study showed a widespread misuse of antibiotics in Northwest Ethiopia. Malpractice such as dose interrupting, sharing of antibiotics for/from the others, and keeping leftover drugs for future use were common among the respondents. These findings suggest that a greater effort is required in public education related to proper and safe uses of antibiotics and that greater efforts are needed to enforce the control of antibiotic use to overcome the emergence of antibiotic resistance.